More Additional Fragments of the Instructions of Suruppak - Civil, Miguel
3N-T 123 = IM 58342, copy; N 3260; 10N-T 21 = A 33687, copy; 3N-T 916, 335; 3N-T 911p = UM 55-21-407; 2N-T 534 = IM 58969; N 3643; N 3707; N 7047